The influence of fermentation time and the presence of salts in the rheology of the fermentation broth of a polysaccharide-producing bacteria free of soil - Bueno, S. M.; Garcia-Cruz, C. H. (Elsevier B.V., 2001)
Rheological studies were carried out in the fermentation broth of a polysaccharide-producing microorganism free of soil. This microorganism was designated 4B. The bacteria 4B was inoculated in the fermentation broth, which consisted of a carbon source and mineral salts, and it was incubated in a rotating agitator at 30 degreesC for 72 h at 210 rpm. A rheometer of concentric cylinders equipped with a thermostatic bath was used and the readings were taken at 25 degreesC. A study was made of the influence of the fermentation time and the readings were made after 24, 48 and 72 h of incubation, using, separately, sucrose and glucose as carbon sources. The influence of the salt concentrations was determined in each carbon source; the salts used were NaCl, KCl and CaCl2 in the concentrations of 0.4%, 1.0%, 2.0% and 3.0%. It was observed that the fermentation broth behaves as a non-Newtonian fluid and it presents pseudoplastic behaviour. Calculations were made of the flow behaviour index (n) and the consistency index (k) of the samples after 24, 48 and 72 h of fermentation, and it was observed that the 72 h sample presented higher k and consequently higher apparent viscosity. of the carbon sources used, the sucrose presented higher viscous broths after 24 and 48 h, and the glucose after 72 h of fermentation. With relation to the effect of the addition of salts, the CaCl2 presented a higher influence on the viscosity of the fermentation broths. (C) 2001 Elsevier B.V. Ltd. All rights reserved.